2020
DOI: 10.3390/ijms21165773
|View full text |Cite
|
Sign up to set email alerts
|

Design, Engineering and Discovery of Novel α-Helical and β-Boomerang Antimicrobial Peptides against Drug Resistant Bacteria

Abstract: In an era where the pipeline of new antibiotic development is drying up, the continuous rise of multi-drug resistant (MDR) and extensively drug resistant (XDR) bacteria are genuine threats to human health. Although antimicrobial peptides (AMPs) may serve as promising leads against drug resistant bacteria, only a few AMPs are in advanced clinical trials. The limitations of AMPs, namely their low in vivo activity, toxicity, and poor bioavailability, need to be addressed. Here, we review engineering of frog deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 177 publications
(253 reference statements)
0
42
0
Order By: Relevance
“…The unique properties of Trp have been harnessed by a large family of short peptides with broad-spectrum antimicrobial activity, commonly referred to as ‘antimicrobial peptides’ or AMPs, essential for host defense and survival. Many AMPs also possess multiple other biological functions, and are therefore, also called host defense peptides (HDPs), such as the ability to regulate inflammation and immunity [ 93 , 95 ]. In several of them, such as members of the ‘temporin’ and ‘aurein’ family, the pairing of Trp and Arg has been shown to be essential for superior activity and bioavailability, as reviewed recently [ 95 ].…”
Section: Interacting Partners Of Trp Residues In a Polypeptidementioning
confidence: 99%
See 1 more Smart Citation
“…The unique properties of Trp have been harnessed by a large family of short peptides with broad-spectrum antimicrobial activity, commonly referred to as ‘antimicrobial peptides’ or AMPs, essential for host defense and survival. Many AMPs also possess multiple other biological functions, and are therefore, also called host defense peptides (HDPs), such as the ability to regulate inflammation and immunity [ 93 , 95 ]. In several of them, such as members of the ‘temporin’ and ‘aurein’ family, the pairing of Trp and Arg has been shown to be essential for superior activity and bioavailability, as reviewed recently [ 95 ].…”
Section: Interacting Partners Of Trp Residues In a Polypeptidementioning
confidence: 99%
“…Many AMPs also possess multiple other biological functions, and are therefore, also called host defense peptides (HDPs), such as the ability to regulate inflammation and immunity [ 93 , 95 ]. In several of them, such as members of the ‘temporin’ and ‘aurein’ family, the pairing of Trp and Arg has been shown to be essential for superior activity and bioavailability, as reviewed recently [ 95 ]. The Trp/Arg amino acid pair is a common theme in many AMPs, where it allows for cation–π interaction as well as the unique side chain properties of the Trp indole ring, mentioned earlier, thereby promoting the formation of the proper higher order structure and interaction with membrane lipid bilayer.…”
Section: Interacting Partners Of Trp Residues In a Polypeptidementioning
confidence: 99%
“…Antimicrobial peptides (AMPs), also known as host defense peptides (HDPs), are a structurally and functionally diverse class of naturally occurring polypeptides that are evolutionarily conserved across all life forms [10][11][12][13][14][15]. AMPs form an integral component of the innate immune system in higher organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The rational substitution of amino acids to generate new HDPs has been explored extensively over the years [ 6 , 7 , 89 , 90 ]. For example, a recent review [ 91 ] has illustrated how peptides can be engineered from HDPs found in nature, e.g., temporins and aureins. This approach is typically used to improve antimicrobial activity and reduce hemolytic activity [ 88 , 92 , 93 ].…”
Section: Comparison Of Lipidation To Other Methods To Increase Biomentioning
confidence: 99%
“…Overall, the process of rational substitution serves to directly reduce MICs and hopefully also improve selectivity, as most approaches optimize activity first and foremost. Compared to the lipidation approach, the substitution of amino acids typically involves the generation of large libraries of peptides (e.g., >5–10 [ 91 ] to multiple hundreds of peptides [ 76 , 96 ]). In contrast, most of the lipidation studies reviewed in Section 2 involved the synthesis of <10 analogs.…”
Section: Comparison Of Lipidation To Other Methods To Increase Biomentioning
confidence: 99%